Necessary and sufficient conditions of optimality in the problems of control with fuzzy parameters - Molchanyuk, I. V.; Plotnikov, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We study the problem of high-speed operation for linear control systems with fuzzy right-hand sides. For this problem, we introduce the notion of optimal solution and establish necessary and sufficient conditions of optimality in the form of the maximum principle.